Pre‐analytical protocol for measuring Alzheimer's disease biomarkers in fresh CSF. Issue 1 (18th December 2020) - Hansson, Oskar; Rutz, Sandra; Zetterberg, Henrik; Bauer, Ekaterina; Hähl, Teresa; Manuilova, Ekaterina; Mert, Mehmet Can; Wahl, Simone; Blennow, Kaj; Stomrud, Erik
Abstract: Introduction: We aimed to establish a standardized, routine‐use pre‐analytical protocol for measuring Alzheimer's disease (AD) biomarkers in cerebrospinal fluid (CSF). Methods: The effect of pre‐analytical factors (sample collection/handling/storage/transportation) on biomarker levels was assessed using freshly collected CSF. Tube type/sterilization was assessed using previously frozen samples. A low‐bind false‐bottom tube (FBT, Sarstedt) was used for all experiments, except tube types/sterilization experiments. Biomarkers were measured using Elecsys CSF assays. Results: Amyloid beta (Aβ)1‐42 levels varied by tube type, using a low‐bind FBT reduced variation. Aβ1‐42 levels were higher with no mixing versus roller/inversion mixing. Aβ1‐42 levels were lower with horizontal versus upright transportation; this was resolved by maximal tube filling and storage at 2°C to 8°C. Aβ1‐40 levels were less strongly affected. Phospho‐tau and total‐tau levels were largely unaffected. Discussion: We propose an easy‐to‐use, standardized, routine‐use pre‐analytical protocol, using low‐bind FBTs, for measuring AD CSF biomarkers in clinical practice.